KOMPOSISI MAKANAN (DIET) DUA SPESIES KODOK BUFO MELANOSTICTUS, SCHNEIDER (1799) DAN BUFO ASPER, GRAVENHORST (1829) DI DARATAN TINGGI DAN DATARAN RENDAH SUMATERA BARAT - Wati, Meliya; Hidayat, Yosmed (Jurnal Pelangi : Research of Education and Development, 2014)
An abiotic factor is one of the different factors in the composition of food, including frogs. The purpose of this research was to determine the composition of the diet or the food and habitat Two Toads Species Bufo (Phrynoides) asper and Bufo (Duttaphrynus) melanostictus in the Highlands and Lowlands of West Sumatra. The sampling used direct collecting method on the site (Ruler and Iskandar, 2003) and research method refers to methods of Sole et.al. (2005) by analyzing the stomach contents of frogs and counting the number and type of animals eaten. Results of the analysis describes the comparison of animals eaten by frog based on the type and location of the research. The results show that the composition of the highest food contained in the stomach B. melanostictus derived from Plateau. Most insects eaten by frogs are ordo of Hymenoptera of the family Formicidae. Food composition ratio between the two frog species show that B melanostictus has the highest food composition compared to B. asper.